Pengaruh Komitmen Organisasi dan Kepuasan Kerja Terhadap Kinerja Karyawan pada CV. Juanda Group - Sindi Anik Fironika; Ratnawati Marginingsih (Lokawati : Jurnal Penelitian Manajemen dan Inovasi Riset, 2023)
Human resources are all employees of a company who want to feel comfortable and happy. When working, an employee must have a big commitment to the company to be able to assist the company in achieving the expected goals, ,and the company must also foster job satisfaction for its employees. This study aims to determine the effect of organizational commitment and job satisfaction on. This study is descriptive with a quantitative approach method, validity test, reliability test, classic assumption test, multiple linear regression test, coefficient of determination test, t-test, and f-test. The results of this study indicate that organizational commitment has a significant impact on employee performance, with the results of the t-test being 10.613 > t-table 2.01174 with a significant level of 0.00 <0.05. Job satisfaction significantly impacts employee performance,with the results of t count 7.731 > t table 2.01174 with a significant level of 0.00 <0.05. The results of testing the independent variable’s simultaneous influence on the dependent variable obtained a value of Fcount = 158.967 > Ftable value of 3.20, so that means there is a positive and significant influence between organizational trust in job satisfaction and CV employee performance. Juanda Group JR Petshop Branch.